2016
DOI: 10.1371/journal.pone.0163793
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth Prevention Post-Conization: A Model of Cervical Length Screening with Targeted Cerclage

Abstract: Women with a history of excisional treatment (conization) for cervical intra-epithelial neoplasia (CIN) are at increased risk of preterm birth, perinatal morbidity and mortality in subsequent pregnancy. We aimed to develop a screening model to effectively differentiate pregnancies post-conization into low- and high-risk for preterm birth, and to evaluate the impact of suture material on the efficacy of ultrasound indicated cervical cerclage. We analysed longitudinal cervical length (CL) data from 725 pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 42 publications
2
30
0
2
Order By: Relevance
“…We, and others, have demonstrated associations between the bacterial community structure of the vaginal microbiome, and the risk and outcome of spontaneous preterm labour and PPROM . We have also shown that cervical cerclage is effective in preventing PTB in women with mechanical damage to their cervix caused by ablative treatment for cervical intraepithelial neoplasia . We therefore hypothesised that women presenting with silent cervical dilation represent at least two aetiological groups.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We, and others, have demonstrated associations between the bacterial community structure of the vaginal microbiome, and the risk and outcome of spontaneous preterm labour and PPROM . We have also shown that cervical cerclage is effective in preventing PTB in women with mechanical damage to their cervix caused by ablative treatment for cervical intraepithelial neoplasia . We therefore hypothesised that women presenting with silent cervical dilation represent at least two aetiological groups.…”
Section: Discussionmentioning
confidence: 90%
“…7 We have also shown that cervical cerclage is effective in preventing PTB in women with mechanical damage to their cervix caused by ablative treatment for cervical intraepithelial neoplasia. 7,26 We therefore hypothesised that women presenting with silent cervical dilation represent at least two aetiological groups. In one group, cervical dilation occurs because of untimely cervical remodelling driven by inflammation resulting from adverse host:microbe interactions in the cervicovaginal and/or lower uterine space.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to assess whether the largest and most comprehensive study on preterm birth clinics (Care 2019) [23] included all UK clinics described in other studies. All but four clinics in the Care 2019 study were identified and alternative studies including them were excluded from synthesis [25][26][27][28][29][30][31][32][33][34][35]. Of the four clinics reported anonymously in the Care 2019 study, three are also believed to have been reported elsewhere and so these studies were also excluded [24,36].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Of the 20 included studies, 15 were full text articles [23, 24, 27-29, 33, 34, 49-56] and five were conference abstracts [26,[30][31][32]36]. Fourteen studies reported on an individual clinic [27-33, 36, 49-53, 56] and six studies reported on multiple clinics [23,24,26,34,54,55]. There were a variety of study designs; seven retrospective audits [26,[28][29][30][31][32]51], three prospective observational studies [24,36,55], two cross-sectional studies [23,49], two prospective cohort studies [54,56], two retrospective cohort studies [50,52], two other retrospective observational studies [27,34], one randomised controlled trial [53], and one qualitative interpretive study [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Correlation of the specific biochemical markers in the produced spectra with the outcomes of subsequent pregnancies in the future may allow the detection of women at high risk of preterm birth and enable the selection of women at high risk that would benefit from intensive antenatal surveillance when pregnant31. Furthermore, further exploration of the mechanistic aspects leading to these changes in the metabolic spectra may permit the use of more targeted cause-directed preventative treatment in the future.…”
Section: Discussionmentioning
confidence: 99%